Estimation of kinetic parameters of anthocyanins and color degradation in vitamin C fortified cranberry juice during storage. (April 2017) - Roidoung, Sunisa; Dolan, Kirk D.; Siddiq, Muhammad
Abstract: Color degradation in cranberry juice during storage is the most common consumer complaint. To enhance nutritional quality, juice is typically fortified with vitamin C. This study determined effect of gallic acid, a natural antioxidant, for the preservation of anthocyanins (ACYs) and color, and estimated kinetics of ACYs and color degradation. Juice, fortified with 40–80 mg/100 mL vitamin C and 0–320 mg/100 mL gallic acid, was pasteurized at 85 °C for 1 min and stored at 23 °C for 16 days. Total monomeric anthocyanins and red color intensity were evaluated spectrophotometrically and data were used to determine degradation rate constants ( k values) and order of reaction ( n ) of ACYs and color. Due to high correlation, k and n could not be estimated simultaneously. To overcome this difficulty, both n and k were held at different constant values in separate analyses to allow accurate estimation of each. Parameters n and k were modeled empirically as functions of vitamin C, and of vitamin C and gallic acid, respectively. Reaction order n ranged from 1.2 to 4.4, and decreased with increasing vitamin C concentration. The final model offers an effective tool that could be used for predicting ACYs and color retention in cranberry juice during storage. Highlights: Anthocyanin degradation was measured and modeled in vitamin C fortified cranberry juice. Kinetic parameters were estimated by using an inverse method of ordinary least squares. Innovative statistical methods were performed to overcome high correlation between parameters. The results of this study would be helpful for the juice industry to predict color and anthocyanin retention during storage. Graphical abstract: